CRTC1‐TRIM11 fusion defined melanocytic tumors: A series of four cases. (9th July 2019) - Ko, Jennifer S.; Wang, Lin; Billings, Steven D.; Pissaloux, Daniel; Tirode, Franck; Berry, Ryan; De La Fouchardiere, Arnaud
Abstract: A cutaneous melanocytic tumor with morphologic overlap with clear cell sarcoma, but defined by CRTC1‐TRIM11 gene fusion, was recently described in a series of five adult patients. Here, we expand the clinicopathologic features of this entity by four additional cases which include pediatric presentation, exophytic growth, and propensity to occur on the head. Patients (2F; 2M) had a median age of 41 years (range 11‐59). Sites of involvement included leg, ear, and face. Tumors were circumscribed, unencapsulated, mostly limited to the dermis, and varied from 5 to 35 mm. One case was exophytic. Lesional cells were arranged in nests and fascicles, and were monomorphic and fusiform with moderate pale to clear cytoplasm, occasional nuclear pseudo‐inclusions, and small to prominent nucleoli. Mitotic rate was variable (rare to 12/10 HPF, median 3/10 HPF). The pediatric case showed increased nuclear pleomorphism, tumor necrosis, and mitotic figures. All cases showed strong, diffuse nuclear staining for SOX10, but were negative or focal for S100 protein, HMB45 and Melan‐A expression. Cases were positive by FISH technique and/or RNA sequencing for a TRIM11 rearrangement/fusion, and negative for EWSR1 rearrangement. This series is presented to aid in further characterization of this novel melanocytic tumor.